FLC and SVP Are Key Regulators of Flowering Time in the Biennial/Perennial Species Noccaea caerulescens - Wang, Yanli; Severing, Edouard I.; Koornneef, Maarten; Aarts, Mark G. M. (Frontiers in Plant Science, 2020)
The appropriate timing of flowering is crucial for plant reproductive success. Studies of the molecular mechanism of flower induction in the model plant Arabidopsis thaliana showed long days and vernalization as major environmental promotive factors. Noccaea caerulescens has an obligate vernalization requirement that has not been studied at the molecular genetics level. Here, we characterize the vernalization requirement and response of four geographically diverse biennial/perennial N. caerulescens accessions: Ganges (GA), Lellingen (LE), La Calamine (LC), and St. Felix de Pallières (SF). Differences in vernalization responsiveness among accessions suggest that natural variation for this trait exists within N. caerulescens. Mutants which fully abolish the vernalization requirement were identified and were shown to contain mutations in the FLOWERING LOCUS C (NcFLC) and SHORT VEGETATIVE PHASE (NcSVP) genes, two key floral repressors in this species. At high temperatures, the non-vernalization requiring flc-1 mutant reverts from flowering to vegetative growth, which is accompanied with a reduced expression of LFY and AP1. This suggested there is “crosstalk” between vernalization and ambient temperature, which might be a strategy to cope with fluctuations in temperature or adopt a more perennial flowering attitude and thus facilitate a flexible evolutionary response to the changing environment across the species range.